一种考虑多方利益均衡的配电网协调运行策略制定方法 (2023)
本发明公开了一种考虑多方利益均衡的配电网协调运行策略制定方法，该策略能够协调分布式电源运营商、配电公司以及电采暖用户三个主体之间的利益冲突，满足各利益主体具有的优化目标和主动发用电要求。本发明能够协调各方利益，减少网损，促进新能源消纳，实现配电网的高效公平运行。 The invention discloses a power distribution network coordinated operation strategy making method considering multi-party benefit balance. The strategy can coordinate the benefit conflicts among three subjects, namely a distributed power supply operator, a power distribution company and an electric heating user, and meets the optimization target and the active power generation and utilization requirements of each benefit subject. The method can coordinate the interests of all parties, reduces the network loss, promotes the new energy consumption, and achieves the efficient and fair operation of the power distribution network.